Influence of setting time and compressive strength for coal bottom ash as partial cement replacement in mortar - Al Biajawi, Mohammad I.; Rahimah, Embong (School of Renewable Energy, Maejo University, 2023)
Environmental degradation from forestry practices to extract limestone from mountains, as well as subsequent calcination in cement factories and dumping of coal bottom ash (CBA) waste from thermal power plants, are among the wastes from industry. However, it is essential for the construction industry to look for sustainable solutions to mitigate the negative impact on the environment. In order to promote an environmentally friendly and sustainable ecosystem, the use of recycled CBA waste as a partial substitute for cement in the manufacturing process has significant potential to mitigate the environmental damage caused by the two distinct sectors of cement and waste management. A series of six mortar preparations were prepared, each containing varying percentages of CBA as a partial substitute for cement. The percentages used ranged from 0% to 50% by weight of cement. The time tests were performed on freshly prepared pastes. All samples were cured with water until the respective test time was reached. The experiment included the evaluation of the compressive strength of hardened mortar cubes at three different time intervals: 7, 14 and 28 days. The findings of the study demonstrate that the incorporation of CBA as a partial substitute for cement affects both the setting time and the compressive strength of the mortar. It has been shown that the use of up to 20% CBA as a cement replacement effectively increases the compressive strength of the mortar. Conclusively, the successful use of CBA as a partial substitute for cement in the manufacture of mortar has the potential to reduce the amount of cement consumed, eliminate the need for landfill space for waste disposal, and contribute to the production of a more sustainable environment, thereby promoting a better lifestyle for the surrounding population.